(untitled) (Journal of Hama University, 2025)
The research aims to identify the degree of availability of administrative empowerment dimensions for principals in primary schools in Hama city from the point of view of the principals themselves, and to identify the most prominent obstacles that limit its application. The research community consisted of all principals of primary schools in Hama city, while the research sample consisted of (71) male and female principals. To achieve the research objectives, the researcher prepared a questionnaire directed to primary school principals, which included in its final form (39) paragraphs distributed over two axes (the axis of administrative empowerment dimensions, which includes the dimension of delegation of powers, the dimension of effective communication, and the dimension of participation in decision-making - the axis of administrative empowerment obstacles for principals, which includes administrative, technical, and personal obstacles). The researcher followed the descriptive analytical approach, and the research reached several results, the most important of which are: - The degree of availability of the dimensions of administrative empowerment for principals in primary schools in Hama city from the point of view of the principals themselves was average, where effective communication came first with a high degree, then participation in decision-making with a medium degree, and finally delegation of powers with a medium degree. - The degree of appreciation of the principals of primary schools for the obstacles to implementing administrative empowerment for principals in Hama city from their point of view was high, where technical obstacles occupied the first place, followed by administrative obstacles, and then personal obstacles in the last place.